THE RELATIONSHIP BETWEEN LEARNING EXPERIENCES IN THE HUMAN MOVEMENT SYSTEM AND STUDENTS’ LEARNING OUTCOMES AND SPORTS HABITS - Lestari, Milleny Aprilia; Pertiwi, Kartika Ratna (Jurnal Edukasi Biologi, 2025)
This study aims to (1) determine students' learning experiences on the material of the human motor system; (2) determine students' learning outcomes on the material of the human motor system; (3) determine students' exercise habits; (4) determine the relationship between learning experiences on the material of the human motor system and student learning outcomes; (5) determine the relationship between learning experiences on the material of the human motor system and student exercise habits. This study employs a quantitative data analysis approach in a survey study. A sample of 124 students was selected using the Census technique. Data distribution utilised a Likert scale questionnaire for the variables of learning experience and exercise habits, and test questions for the variable of learning outcomes. Data analysis techniques employed include descriptive statistical analysis, normality tests, linearity tests, Pearson correlation tests, and cross-tabulation. The results of the study: (1) students' learning experiences are in the moderate category (39%); (2) students' learning outcomes are in the moderate category (44%); (3) students' exercise habits are in the moderate category (40%); (4) there is no relationship between learning experiences on the material of the human motor system and student learning outcomes; (5) There is a positive relationship between the experience of learning about the human movement system material and students' exercise habits with a moderate relationship (significance value 0.000 0.005 with a correlation degree of 0.454). Teachers can utilise this research as a means to provide contextual biology learning experiences for students, particularly in the area of movement systems.